PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR OPERASI HITUNG BILANGAN CACAH KELAS V SDN PASUCEN 02 (JURNAL ILMIAH PENDAS: PRIMARY EDUCATION JOURNAL, 2024)
The low learning outcomes of students on the material of counting operation of numerical numbers is the reason this research was conducted. This research is a classroom action research (PTK) which has the aim to find out that after the Problem Based Learning (PBL) model is applied to the material of counting operations of small numbers up to 100,000 shows an increase in learning outcomes. The focus of this research is the steps of applying PBL that affect student activeness and learning outcomes. The data collection techniques used include interviews, tests, observations, and documentation. The research subjects in this study were the class teacher and 30 students in class V. The research was carried out in two cycles with cycle I on addition and subtraction operations with the help of the media of the stick board for small numbers and cycle II on multiplication and division with the help of snakes and ladders media. In cycle I, the increase in learning outcomes reached ≥10% and 24 students were complete but student activeness and teacher learning effectiveness had not reached ≥75%. In cycle II, it showed that there was a ≥10% increase in learning outcomes and as many as 24 students achieved a complete score as well as student activeness and the effectiveness of teacher learning had reached ≥75%. Based on this description, it means that the application of the PBL model can improve the learning outcomes of mathematics counting operation material for class V SDN Pasucen 02.
Keywords: hasil belajar; operasi hitung; Problem Based Learning